Water state changes during the composting of kitchen waste. (April 2015) - Shen, Dong-Sheng; Yang, Yu-Qiang; Huang, Huan-Lin; Hu, Li-Fang; Long, Yu-Yang
Highlights: Entrapped and capillary water content changed in composting of kitchen waste. Percentage entrapped water indicated degree of composting of kitchen waste. Entrapped water was affected by the presence of hemicellulose and cellulose. Abstract: Changes in water states during the composting of kitchen waste were determined. Three experiments, R 55, R 60, and R 65, with different initial moisture contents, 55%, 60%, and 65%, respectively, were performed. Three water states, entrapped water (EW), capillary water (CW), and multiple-molecular-layer water (MMLW), were monitored during the experiments. Changes only occurred with the EW and CW during the composting process. The percentage of EW increased, and the percentage of CW decreased as the composting process progressed. The R 60 experiment performed better than the other experiments according to changes in the temperature and carbon-to-nitrogen ratio (C/N). The percentage of EW correlated well ( P < 0.05) with the dissolved organic carbon content (DOC), electrical conductivity (EC), pH, and C/N, and was affected by the hemicellulose and cellulose contents.